Rural infrastructure and smallholders commercialization: analysis of crop input market from Jimma Zone, South-West Ethiopia - Alemu, Minyahil; Dachito, Amsalu (Goodwood Publishing, 2020)
Purpose: This study is aimed to examine the effect of rural infrastructure on smallholders’ crop input market participation with reference to Jimma zone. Research methodology: Censored Tobit approach was employed to model relationships between the degree of household market participation from input side and rural infrastructures. Results: Distance to the nearest all-weather-road from the farm area was found important. Moreover, provision of rural credit, communication and rural market services was found to significantly foster smallholder commercialization. Unfortunately, we estimated trivial coefficient for agricultural extension. Limitation: This study is limited to a year data, where we are unable to estimate the long term impact of rural infrastructural service on rural commercialization. Contribution: Various inadequacies in the provision of services may likely be involved. The right approach for the future should consider efficiency as well as the adequacy of the services being provided. It would be better to provide smallholders with the necessary infrastructures to ensure growth as well as the transformational targets. Besides, interventions intensifying rural access to information are vital. Keywords: Censored Tobit, Commercialization, Crop input Market index, Infrastructure, Smallholder